2022
DOI: 10.1039/d1qo01819a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of novel P-chiral monophosphorus ligands

Abstract: A series of novel P-stereogenic monophosphorus ligands (Xie-phos) were synthesized via the hydrophosphinylation of alkynes with secondary phosphine oxides by palladium catalysis and the following base mediated cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The addition of the secondary phosphine oxide to terminal and internal alkynes produced alkenylphosphine oxides 29 in good to excellent chemo-, regio-, and enantioselectivities and recovered secondary phosphine oxides. The practicability of this method was extended to the subsequent base-mediated cyclization of P-chiral o -methylphenyl alkenylphosphine oxides 31 to build a class of novel P-chiral monophosphine compounds based on the dihydrobenzophosphole backbone (called Xie-Phos) . Then, we found that palladium/Xiao-Phos ( X1 or X2 ) efficiently catalyzed the kinetic resolution reaction of racemic secondary phosphine oxides via P-benzylation, simultaneously affording P-chiral tert - and sec -phosphine oxides 30 in good yields with high enantioselectivities (a selectivity factor of up to 226.1) …”
Section: Coupling Reactionsmentioning
confidence: 99%
“…The addition of the secondary phosphine oxide to terminal and internal alkynes produced alkenylphosphine oxides 29 in good to excellent chemo-, regio-, and enantioselectivities and recovered secondary phosphine oxides. The practicability of this method was extended to the subsequent base-mediated cyclization of P-chiral o -methylphenyl alkenylphosphine oxides 31 to build a class of novel P-chiral monophosphine compounds based on the dihydrobenzophosphole backbone (called Xie-Phos) . Then, we found that palladium/Xiao-Phos ( X1 or X2 ) efficiently catalyzed the kinetic resolution reaction of racemic secondary phosphine oxides via P-benzylation, simultaneously affording P-chiral tert - and sec -phosphine oxides 30 in good yields with high enantioselectivities (a selectivity factor of up to 226.1) …”
Section: Coupling Reactionsmentioning
confidence: 99%
“…Figure presents all the P-stereogenic monophosphorus ligands reported from 2001 to 2023. ,,,,,,,,,, …”
Section: A Historical Overview Of P-stereogenic Phosphorus Ligandsmentioning
confidence: 99%
“…In 2022, this protocol was employed by the same group to assemble a set of novel P-chiral monophosphorus ligands (Xie-phos) 14. [10] The benzophospholane framework was rapidly synthesized via a simple base-mediated intramolecular cyclization from P-stereogenic adducts 12. The obtained products 14 served as efficient ligands in many catalytic asymmetric reactions (such as α-arylation of amides and the domino Heck/Suzuki reaction).…”
Section: Asymmetric Addition To Activated Alkenes or Alkynesmentioning
confidence: 99%